Mergers and Acquisitions in Selected Frontier Markets of Asia - Farhan Ahmed; Afzal Ahmed; Sahabia Kanwal (Signifikan: Jurnal Ilmu Ekonomi, 2018)
This paper aims to provide contemporary and comparative information on mergers and acquisition activities. The findings have shown that Vietnam is very active in mergers and acquisitions activities, for instance in Vietnam 2946 transactions were announced, and 2114 completed in the last decade. Furthermore, Vietnam has a distinctive element of merging local firms; Out of top 20 deals, in 18 transactions target firms and acquirer both were from Vietnam. On the other hand, Sri Lanka has the highest percentage of completed M&A transactions in the last decade compared to Pakistan and Vietnam. In case of Pakistan, the findings suggest that Pakistan has had the highest number of value-based Mergers and Acquisitions deals in comparison to Sri Lanka and Vietnam. Interestingly, even though the number of transactions is higher compared to Sri Lanka and Vietnam; however, mergers and acquisition have had no significant impact on the profitability of Pakistan companies.DOI: 10.15408/sjie.v7i1.6074